A Semiotic Approach to the Analysis of the News Story - رسن, نزار عبد الغفار; عباس, علاء الدين أحمد (ALBAHITH ALALAMI, 2016)
This study attempts to provide an approach analysis for the news, depending on the bases and principles which conceptuality semiotic researchers of this field first of them «A. J. Gremas» for the theory of «narrative discourse analysis», to more clarify we tried to apply it on a published press- news, to concludes the most important steps and methods that are necessary to follows gain more understanding of the press- news.